2012
DOI: 10.1002/0471140864.ps2905s68
|View full text |Cite
|
Sign up to set email alerts
|

HPLC‐SEC Characterization of Membrane Protein‐Detergent Complexes

Abstract: Determination of the oligomeric state of integral membrane proteins in detergent solutions is a challenging task because the amount of detergent associated with the protein is typically unknown and unpredictable. Methods that estimate the molecular weight of proteins from their hydrodynamic properties in solution are not suitable for detergent-solubilized membrane proteins. However, size-exclusion chromatography (SEC) performed in combination with analyses of static light scattering (SLS), ultraviolet absorban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…1 D ) indicated that the protein was of high monodispersity, with an apparent M r of ∼500 kDa. Although the subunit structure of membrane proteins cannot be determined by gel filtration ( 24 ), the similar size obtained by BN/PAGE supported that the TMEM16F protein existed as a homodimer.…”
Section: Resultsmentioning
confidence: 94%
“…1 D ) indicated that the protein was of high monodispersity, with an apparent M r of ∼500 kDa. Although the subunit structure of membrane proteins cannot be determined by gel filtration ( 24 ), the similar size obtained by BN/PAGE supported that the TMEM16F protein existed as a homodimer.…”
Section: Resultsmentioning
confidence: 94%
“…The presence of all expected proteins in the elution peaks was checked by immuno-blotting. Interpreting these large apparent molecular masses is however challenging, as the extracellular domain of DivIB, DivIC, FtsL, PBP2x are elongated [23,47,52,53] and the estimation of the molecular mass of proteins from their hydrodynamic properties in solution is not suitable for detergent-solubilized membrane proteins [54]. However, DivIB and the H-DivIB/DivIC/FtsL complex eluted in two peaks, indicating that these entities could form dimers.…”
Section: Resultsmentioning
confidence: 99%
“…By far the most common applications are establishing whether a purified protein is monomeric or oligomeric and the degree of oligomerization, and assessing aggregates 3,10,11,17,31,36,37,38 . The ability to do so for detergentsolubilized membrane proteins that cannot be characterized by traditional means is especially prized, and detailed protocols for this have been published 31,39,40,41,42,43 . Other common applications include establishing the degree of post-translational modification and polydispersity of glycoprotein, lipoproteins and similar conjugates 4,31,44,45,46,47 ; the formation (or lack thereof) and absolute stoichiometry (as opposed to stoichiometric ratio) of heterocomplexes including protein-protein, protein-nucleic acid and protein-polysaccharide complexes 24,46,48,49,50,51,52 ; determining the monomer-dimer equilibrium dissociation constant 49,53,54 ; and evaluating protein conformation 55,56 .…”
Section: Introductionmentioning
confidence: 99%